Impact of online advertising and the use of cosmetic products: a study on the influence of online advertisements and change in the purchasing behaviour of women in Kerala - Ashiqha Sultana (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
Online advertisements have created a great impact among the common people and their purchasing habits with the substantial rise of internet usage. The online retailing particularly in India is in a transition stage where most of the brands are leaving the traditional store format. Online advertising has different parameters that contributes to the consumer buying behaviour. The online retailing in India grows bigger each day with the emergence of new brands and online shopping sites, women consumers play an important role and their buying behaviour is significant with regard to the growth of online shopping through various platforms and applications. In that respect, Online advertising through social media is on a fast-developing pace and advertisements through various platforms like Instagram, Facebook, YouTube and other shopping apps like Nykaa, Sephora, Amazon, Myntra etc gives innumerable shopping opportunities for women with different national and international cosmetic brands. Online advertising influenced the women in Kerala to come out of the shell and thus created a need on their minds. The basic question is how online advertising attract female consumers to online/ social media platforms. This study aims to determine various factors affecting preference of female consumers for different cosmetic brands and majorly focused on the influence of online advertisements among women in Kerala and the changes in their purchasing behaviour. The major findings of the study indicate the huge effect of online advertising on choosing cosmetic brands by women through online platforms. The research method used for this particular study is analytical survey. This particular analytical survey attempts to describe and explain the influence of online advertisements and change in the purchasing behaviour of Women in Kerala with regard to the cosmetic products. The result of this particular study allows to examine the interrelationships among variables and to develop explanatory inferences. Findings of the study makes it clear that women in Kerala are receptive to the forms of online ads of cosmetic products on social media platforms and various mobile applications or shopping sites.